Hydrogenation of glucose to sorbitol by using nickel hydroxyapatite catalyst - Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Lakshmi Kantam, Mannepalli (Chemcatchem, 2024)
A series of nickel hydroxyapatite catalysts were synthesized by the co-precipitation method followed by calcination and reduction. These catalysts were employed for the aqueous phase hydrogenation of glucose to sorbitol. The Ni-HAP catalyst with comparatively high surface area and acid-base strength gave high sorbitol selectivity in 1 h. Ni-HAP-4 catalyst with moderate Ni (3.5 wt. %) content having smaller and highly dispersed nickel particles gives an excellent yield of sorbitol, 97 % in 1 h. The Ni-HAP-4 catalyst works well with other polar protic solvents. Different characterization techniques like XRD, TEM, SEM-EDS, BET, NH3-TPD, and CO2-TPD were employed to analyze the Ni-HAP-4 catalyst. A facile hydrogenation of glucose to sorbitol has been reported with Ni-HAP catalyst using water as a solvent. The excellent yield of sorbitol, 97 % in 1 h is possible due to the high surface area and high acid-base strength of the Ni-HAP-4 catalyst. image
Keywords: glucose; Hydrogenation; Hydroxyapatite (HAP); Nickel; Sorbitol